A Study of a Nation-Wide Pilot Program in School Mathematics - Swincicky, K.; Malone, John (Key Centre for School Science and Mathematics, Curtin University of Technology, 2008)
A senior high school in Western Australian participated in the piloting of the National Mathematics Program initiative organised by the International Centre for Excellence. The opportunity to modify the school's Year 8 program and to implement change in the schools feeder primary schools occurred with the second stage of the pilot program's Transition Phase 1 and 2, implemented in 2007. This paper presents an overview of the research methodology and presents some of the findings.